Role of Environment, Nutrition, Microbiota, Mammalian Target of Rapamycin and Dietary Supplements in Autism - Ibrahim, khadiga; El Sayed, Eman; Mahdy-Abdallah, Heba (Archives of Ecotoxicology, 2020)
Autism Spectrum Disorder (ASD) is a developmental disorder with the age of onset under 3 years old. It is characterized by definite impairments in social interactions, speech abnormalities, and stereotyped patterns of behaviors. Although the exact pathology and etiology of ASD are not fully elucidated, exposure to environmental toxins, micronutrients deficiency, dysbiosis and mutation in genes of mammalian target of rapamycin (mTOR) signaling pathway are emerging as risk factors for ASD. Maternal exposure to heavy metals, air pollutants, and pesticides markedly increases the risk of ASD. Many clinical and experimental trials documented that gastrointestinal symptoms and disturbances of the gut microbiota usually accompanied cerebral disorders in autistic patients. Furthermore, studies showed that gene mutations causing hyperactivation of mTOR significantly lead to autistic symptoms. Pharmacological and nutritional interventions revealed a significant improvement in autistic individuals. The use of dietary supplements and the elimination diets exhibit minor or no adverse effects as compared to conventional drugs. In this review article, we tried to summarize some of the etiological factors that predispose to autism. We discussed the possible mechanisms that potentiate autistic symptoms by such factors. Also, we focused on the role of interventions either by various dietary supplements or by elimination diets in the management of autism.